PENGARUH SISTEM PENGENDALIAN INTERNAL, PEMANFAATAN TEKNOLOGI INFORMASI, DAN KOMPETENSI PERANGKAT DESA TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA - Yustika Rezkiyanti (AkMen JURNAL ILMIAH, 2019)
The accountability of village fund management has become a demand for local government. Problems emerging from the accountability of village fund management are related to the internal control system, Utilization of Information Technology and the competence of village officials. This research aims to know and analyze the influence of the internal control system, Utilization of Information Technology and the competence of village officials to accountability of village fund management in takalar Regency. This is a quantitative research study and data were collected by questionnaires. Population and sample are village fund management officers in Takalar Regency with 128 respondents. The hypothesis was tested by multiple linear regression analysis with SPSS application. The findings show that: (1) The Internal Control System has a positive and significant impact on the accountability of village fund management with the significant value 0,018>0,05, (2) Utilization of Information Technology has a positive and significant impact on the accountability of village fund management with the significant value, 0,000>0,05and (3) The competence of village officials has a positive and significant impact on the accountability of village fund management with the significant value 0,000>0,05.